LGBT (LESBIAN, GAY, BI-SEXUAL AND TRANSGENDER) COMMUNITY AROUND THE WORLD - Sayeed Munna, Abu; Iftekhairun Nisa Yusuf, M.M.; Alam, Dr. Tasnim; Hasan Romel, Mahadi (IJRDO - Journal of Social Science and Humanities Research, 2017)
LGBT community and citizens are a major issue in the present world. Day by day their numbers are increasing. Most of the countries of the world are against the rights and protection of this vulnerable number of community people. Religious and social values are playing as the most predominant impediment for the recognition of these sorts of sexually orientated people. In every sphere of the society, they are treated in an inhuman way. It is always obvious that there must be the provision for equal treatment of all citizens. But they are hardly met in case of increasing number of LGBT people. They are not treated as humans among the humans lauding the rhymes of Humanity. Sexual orientations are still penalized with life imprisonment and death penalty. Some good steps have been taken in upholding of the condition and rights of the LGBTs. A remarkable number of human rights organizations are working to improve their social, political and civil status. However, the number is still not enough to meet the requisite assistance needed for this community. Several countries have arranged a congenial atmosphere for this community. Several laws are enacted, some are nulled, and some are amended to secure the rights and protections of this unwanted minority. As a result, the future is better than what they have started from the point of.